IMPLEMENTATION AUGMENTED REALITY IN SENIOR HIGH SCHOOL TO CHALLENGE IN INDUSTRIAL 4.0 - Sukmana, Farid; Rozi, Fahrur (STKIP PGRI Tulungagung, 2018)
Senior High School is one of education in indonesia that has important role in the next generation of technology in 2024. This generation must has a qualification in the next technology. Where are in this time, techology will change student how to learn about all subject in the class. This time is indutrial 4.0 as a time the digitalization, augment reality, 3D printing, big data will be use in next education like in the college. So in this section our article will be explained about the important thing some part of industrial 4.0 to challenge the some student to get knowledge in this generation. So the student will be know about the subjects in senior high school and what function of this subject in next profession after they are graduate in this year (2024). So they ready to learn what knowledge that they must qualificate to challange this era. This article will be compared knowledge of technolgy industrial 4.0 about augment reality and another technolgy. So with this article will be know what aspect technolgy that must implement in Senior High School and to be included in the system of education as a subject in Information Technology.Â